2013
DOI: 10.1051/0004-6361/201321902
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing transient ionization in dynamic events

Abstract: Aims. The present study aims to provide a diagnostic line ratio that will enable the observer to determine whether a plasma is in a state of transient ionization.Methods. We use the Atomic Data and Analysis Structure (ADAS) to calculate line contribution functions for two lines, Si iv 1394 Å and O iv 1401 Å, formed in the solar transition region. The generalized collisional-radiative theory is used. It includes all radiative and electron collisional processes, except for photon-induced processes. State-resolve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 6 publications
1
33
0
Order By: Relevance
“…Doyle et al (2012) and Doyle et al (2013) applied the GCR technique to predict the response of TR lines to short heating bursts occurring at loop footpoints. In Doyle et al (2013), the Si iv 1393.76Å and O iv 1401.16Å lines were studied.…”
Section: -D Hydrodynamic Modellingmentioning
confidence: 99%
See 2 more Smart Citations
“…Doyle et al (2012) and Doyle et al (2013) applied the GCR technique to predict the response of TR lines to short heating bursts occurring at loop footpoints. In Doyle et al (2013), the Si iv 1393.76Å and O iv 1401.16Å lines were studied.…”
Section: -D Hydrodynamic Modellingmentioning
confidence: 99%
“…Doyle et al (2012) and Doyle et al (2013) applied the GCR technique to predict the response of TR lines to short heating bursts occurring at loop footpoints. In Doyle et al (2013), the Si iv 1393.76Å and O iv 1401.16Å lines were studied. It was found that about 0.2 s after the occurrence of the burst, Si iv responds with an intensity increase by a factor of more than three, while the intensity of O iv is increased only weakly.…”
Section: -D Hydrodynamic Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we believe that the presence of plasmas undergoing transient ionization (cf. Doyle et al 2013) can be neglected.…”
Section: Synthetic Spectra For κ-Distributionsmentioning
confidence: 99%
“…The ionization equilibrium is, however, an additional source of uncertainty because of the individual ionization and recombination rates, as well as possible departures from the ionization equilibrium (e.g. Bradshaw et al 2004;Bradshaw 2009;de Avillez & Breitschwerdt 2012;Reale et al 2012;Doyle et al 2012Doyle et al , 2013Olluri et al 2013) at low electron densities. The results presented here highlight the need for spectroscopic observations over a wide wavelength range, especially in the 170 Å − 370 Å range, which include many strongly temperature-sensitive line pairs, such as the Fe ix 244.909 Å/171.073 Å or 244.909 Å/188.497 Å, or analogous combinations from other ions investigated here.…”
Section: Several Forbidden Lines Such As the Fe X 637826 å Linementioning
confidence: 99%